De-extinction and Taking Control of Earth's “Metabolism” - Preston, Christopher J. (The Hastings Center report, 2017)
In a laboratory on a university campus in Santa Cruz, California, Ben Novak is doing everything he can to bring Ectopistes migratorius back from the dead. Using techniques now available in genome reading and gene synthesis, he and paleogenomicist Beth Shapiro hope that, by 2032, a flock of passenger pigeons ten thousand or more strong will have resumed an ecologically significant role in the mast forests of the Eastern United States. Novak knows—and the International Union for Conservation of Nature (IUCN) affirms—that the challenges involved in making de-extinction work are far from solely genetic. Novak is doing an ecological risk assessment of passenger pigeon reintroduction to figure out whether flocks of the resurrected species would pose any special hazards to ecosystems. Ecological harm is one of several worries attending the prospect of de-extinction. Among other concerns are the possible harm that individuals born through this process might suffer and the possible introduction of disease vectors. But I want to step back from these immediate questions and think about some conceptual ones that operate in the background. Technology can be a grand shaper of cultural norms and expectations, and de-extinction should be looked at in relation to a number of emerging technologies. This paper will examine the degree to which de-extinction is part of a more widespread restructuring of ethical relationships to the surrounding world that are under way at the hands of emerging technologies. This restructuring is part of an ongoing shift in how to think about conservation in the new epoch of the Anthropocene.